Two new species of Tanytarsus van der Wulp (Diptera: Chironomidae) from Costa Rica - Reis, Patricia Do Rosario; Gil-Azevedo, Leonardo H.; Ferreira-Keppler, Ruth L. (Zootaxa, 2021)
Tanytarsus is a highly diverse genus of Chironomidae (Diptera), distributed worldwide. In the Neotropics, 84 species are known, but only five have been recorded from Central America to date. In the present article, two new species of the Tanytarsus ortoni species group are described and illustrated based on male specimens collected from Costa Rica, T. braini sp. nov. and T. costarica sp. nov.